Three-stage pattern of rapid increase, plateau, and subsequent decline in vitamin D concentration during pregnancy among Chinese women: a large-scale survey - Wang, Huabin; Zhang, Feifang; Li, Bingxian; Fu, Miao; Shan, Xiaoyun; Ma, Yongjun (Frontiers in Nutrition, 2023)
Background: There is an incomplete understanding of fluctuations in vitamin D (VitD) concentration during pregnancy among Chinese women. Furthermore, previous research has yielded conflicting results in this area. This study aims to investigate the changes in VitD status and deficiency in Chinese pregnant women across various age groups, gestational weeks, and as well as seasonal variations through conducting a large-scale survey.Methods: 11,220 Chinese pregnant women between 2021 and April 2023 were included in this study. Generalized additive models (GAM), stratified analysis, and restricted cubic splines (RCS) were used to analyze changes in VitD status and deficiency risk during pregnancy.Results: Of the participants, 45.2% had deficient concentration of 25-hydroxyvitamin D. VitD concentration and deficiency rate do not show linear changes with age and gestational weeks. With increasing gestational weeks, VitD concentration rapidly increased in women with gestational age < 20 weeks, remained stable between 20-30 weeks, and decreased beyond 30 weeks; however, the odds of VitD deficiency showed three different patterns: a rapid decline, a stable period, and a mild increase, respectively. Based on the stratified regression analysis, VitD deficiency odds increased by 16% with each additional week of gestation in pregnant women with gestational age > 30 weeks, OR = 1.16 (1.10 -1.22), p < 0.001. Interaction effect analysis indicated that pregnant women over 35 years with gestational weeks between 20-30 had the lowest odds of VitD deficiency.3 Conclusion: VitD concentration undergo three phases during pregnancy: rapid increase, plateau, and subsequent decrease. VitD deficiency odds was highest in pregnant women under 25 with gestational ages < 20 and lowest in pregnant women over 35 with gestational ages between 20-30. The odds of deficiency increase slightly in pregnant women with gestational ages beyond 30 weeks, indicating that they may require additional VitD supplementation.